If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6r + 3e + -2d) + (3r + -5e + 3r) + -1(-5r + 4e + -8d) = 0 Reorder the terms: (-2d + 3e + 6r) + (3r + -5e + 3r) + -1(-5r + 4e + -8d) = 0 Remove parenthesis around (-2d + 3e + 6r) -2d + 3e + 6r + (3r + -5e + 3r) + -1(-5r + 4e + -8d) = 0 Reorder the terms: -2d + 3e + 6r + (-5e + 3r + 3r) + -1(-5r + 4e + -8d) = 0 Combine like terms: 3r + 3r = 6r -2d + 3e + 6r + (-5e + 6r) + -1(-5r + 4e + -8d) = 0 Remove parenthesis around (-5e + 6r) -2d + 3e + 6r + -5e + 6r + -1(-5r + 4e + -8d) = 0 Reorder the terms: -2d + 3e + 6r + -5e + 6r + -1(-8d + 4e + -5r) = 0 -2d + 3e + 6r + -5e + 6r + (-8d * -1 + 4e * -1 + -5r * -1) = 0 -2d + 3e + 6r + -5e + 6r + (8d + -4e + 5r) = 0 Reorder the terms: -2d + 8d + 3e + -5e + -4e + 6r + 6r + 5r = 0 Combine like terms: -2d + 8d = 6d 6d + 3e + -5e + -4e + 6r + 6r + 5r = 0 Combine like terms: 3e + -5e = -2e 6d + -2e + -4e + 6r + 6r + 5r = 0 Combine like terms: -2e + -4e = -6e 6d + -6e + 6r + 6r + 5r = 0 Combine like terms: 6r + 6r = 12r 6d + -6e + 12r + 5r = 0 Combine like terms: 12r + 5r = 17r 6d + -6e + 17r = 0 Solving 6d + -6e + 17r = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '6e' to each side of the equation. 6d + -6e + 6e + 17r = 0 + 6e Combine like terms: -6e + 6e = 0 6d + 0 + 17r = 0 + 6e 6d + 17r = 0 + 6e Remove the zero: 6d + 17r = 6e Add '-17r' to each side of the equation. 6d + 17r + -17r = 6e + -17r Combine like terms: 17r + -17r = 0 6d + 0 = 6e + -17r 6d = 6e + -17r Divide each side by '6'. d = e + -2.833333333r Simplifying d = e + -2.833333333r
| k/8=10/12 | | -20s-3-25s-1=0 | | 21+(6/3)x8-1+35 | | 3u+36=-7(u-4) | | 1/6b=7.4 | | (6r+3e-2d)+(3r-5e+3r)-(-5r+4e-8d)= | | 3/p=-11/10 | | 11k+6=4k+34 | | f/-17=51 | | c=8d | | .17n=-51 | | x^2+30=11 | | 10/7=9/m | | 7(2)-2(2+6)=-2 | | 16k^2-9=0 | | X+6x(x+88)=40 | | 5/6=v/7 | | 3(4+x)=x+26 | | 67000*.09+x*.03=.04(67000+x) | | 2(w+3)+5=19 | | 6/12=x/2 | | X+47(107+x)=140 | | 3y-1=9x | | 1/8+y=-3/16 | | -9+2z=9z-1+13 | | 8(n+5)=96 | | Sec^4x-2tan+1=0 | | -7(7x+4)+7x=-196 | | 6(x+1)=20-x | | 9x+64=-144-17x | | (A)(b)=(b)(a) | | -9+2z=9z-1+3 |